Renewable Energy Consumption Impact on the Lebanese Economy - Taher, Hanadi (International Journal of Energy Economics and Policy, 2017)
This study examines the impact of renewable energy consumption on economic growth for Lebanon over the period 1990–2012. The renewable energy consumption with negative coefficient and statistically significant while the real gross fixed capital formation, and the labor force with the respective coefficients positive and statistically significant. The research data is from the Lebanese central bank, the International Monetary Funds and the World Development Indicators then it is regressed in basic time series analysis taking into consideration the different variables that have an influence on the economic growth. After testing its robustness and illustrated through ARMAX, the results show a statistically significant impact of renewable energy consumption on the Lebanese economic growth. Keywords: Renewable Energy consumption, energy consumption, Lebanese economic growth JEL Classifications: O440; Q280